Changes in the use of alcohol and tobacco in Slovenia during the first wave of the SARS-COV-2 pandemic - Krnel Sandra Radoš; Kilian Carolin; Keršmanc Marjetka Hovnik; Roškar Maja; Koprivnikar Helena (Sciendo, 2022)
In the first months of 2020, the SARS-CoV-2 virus spread all over the world and numerous measures were adopted that had a strong impact on both personal and public life. This contribution explores changes in alcohol and tobacco use during the first months of the COVID-19 pandemic in Slovenia.